KEPATUHAN TERAPI KELASI BESI DAN KUALITAS HIDUP ANAK DENGAN THALASSEMIA MAYOR - Rilla, Eldessa Vava; Fauzan, Suhaimi (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Thalassemia is a genetic blood disorder characterized by a deficiency of globin chains in hemoglobin. One of the main problems in patients with thalassemia is non-adherence to iron chelation therapy. As a lifelong chronic disease, thalassemia requires continuous treatment, including iron chelation therapy, which functions to remove excess iron accumulation in the body due to routine blood transfusions through feces and urine. Adherence to this therapy plays an important role in improving the quality of life of patients. Objective: To determine the relationship between adherence to iron chelation therapy and quality of life in children with thalassemia at RSUD dr. Slamet Garut. Methods: This study used a descriptive analytic design with a quantitative approach and a correlation study design. The sample consisted of 96 respondents selected using a purposive sampling technique. Data were collected to assess adherence to iron chelation therapy and the quality of life of respondents. Data analysis was performed using univariate and bivariate analysis to determine the relationship between variables. Results: The results showed that almost all respondents (95.8%) were not adherent to iron chelation therapy, and the majority of respondents (92.7%) had a poor quality of life. Statistical analysis showed a significant relationship between adherence to iron chelation therapy and quality of life in children with thalassemia, with a p-value of 0.01 (p < 0.05). Conclusion: There is a relationship between adherence to iron chelation therapy and the quality of life in children with thalassemia. Good adherence to therapy can help improve quality of life, optimize growth and development, and prolong the survival of children with thalassemia.